The relationship between leadership style and employee engagement in Sasol Gas, South Africa - Duma, Thobile (Rhodes University, Faculty of Commerce, Rhodes Business School, 2010)
The main purpose of this study was to determine whether there is a significant relationship between leadership styles of Sasol Gas leaders and their followers' level of employee engagement. The instruments used in the study were the Multifactor Leadership Questionnaire (MLQ) (Form 5X) and the Utrecht Work Engagement Scale (UWES 9). The MLQ (5X) was completed by the followers and leaders of Sasol Gas to determine whether Sasol Gas leaders use transactional, transformational and/or laissez-faire leadership styles. The work engagement instrument was completed by each follower to determine current levels of employee engagement. Descriptive statistics were obtained and correlations completed for the data to determine whether the different leadership styles exhibit different levels of engagement. The MLQ survey results indicate that leaders of Sasol Gas have more transformational than transactional leadership styles. The UWES 9 measured the three factors of vigour, dedication, and absorption; dedication had the highest mean compared to vigour and absorption, indicating that Sasol Gas employees strongly identify themselves with their work because it is experienced as meaningful, inspiring, and challenging. This research found a statistically significant, albeit weak, relationship between transformational and transactional leadership styles and employee engagement. This is a positive reflection of the current Sasol Gas leaders because empirical evidence shows that transformational leadership behaviours are more successful for attaining and fulfilling goals during organisational change.
Keywords: Uncatalogued